Delegation of quality control in value chains - Saak, Alexander E. (International Food Policy Research Institute, 2016)
This paper studies the decision of a firm that sells an experience good to delegate quality control to an independent monitor. In an infinitely repeated game consumers’ trust provides incentives to (1) acquire information about whether the good is defective and (2) withhold the good from sale if it is defective. If third-party reports are observable to consumers, delegation of monitoring lessens the first and dispenses with the second moral hazard concern but also creates agency costs due to either limited liability or lack of commitment. In equilibrium the firm controls quality without an independent monitor only if trades are sufficiently frequent and consumer information about quality is sufficiently precise. This result holds under different assumptions about feasible contracts, collusion, verifiability of reports, joint inspections, and the number of firms that hire the third-party monitor. If third-party reports are not publicly observed, delegation can be optimal only if two or more firms hire the third-party monitor because then both moral hazard concerns are present under delegation.